Study of capital structure and ownership concentration on the agency costs of firms listed under the shariah-compliant securities (1998 - 2006) / Athirah Nor Mustafa - Mustafa, Athirah Nor (2007)
paper measures the relationship between capital structure, ownership concentration and agency costs. Therefore, the aim of this study is to examine whether capital structure and ownership concentration have significant influence on a firm's agency costs. A sample size Of 26 Shariah-compliant securities will be chosen in this study for the period of nine years that is from 1998 to 2006. The data collected Will be measured using multiple regression model. Agency costs exist When there is a conflict Of interest between the shareholders and the managers. They will have different goals towards the organization and they have different attitudes towards risks. Agency costs will be measured using the asset turnover ratio and return on equity ratio. There are two main expected findings. (i) It is that a firm With a high debt level will decrease its agency costs, and (ii) there is a positive relationship between the largest shareholder concentration and the agency costs.